Financial Services Authority (OJK) Policy on Debt Proportion and Its Impact on the Profitability of DES Listed Companies in Indonesia - Hadiah, Aida Nurul (Shirkah: Journal of Economics and Business, 2016)
The sharia capital market in Indonesia has different principles and criteria from the conventional capital market, and focuses on “ethics and justice”. The desired outcomes of capital market transactions should be in accordance with Islamic ethics and norms as managed in sharia. OJK (Otoritas Jasa Keuangan/ Financial Services Authority) is supervisor and manager of financial service activities in the banking sector, the capital market sector, and the IKNB (Industri Keuangan Non-Bank/ Non-Bank Financial Industry) sector. The research object is capital structure, leverage, and profit. They are managed by size, liquidity, growth, and active structure of the listed company at sharia stock. The research population is 24 companies excluded from the OJK due to a lack of criteria in their 2013-2015 quarterly financial reports. The data analyses used are descriptive statistics and inferential statistics. This analysis finds the effect of the independent variable, dependent variable and control variable simultaneously and partially. The research result shows that capital structure and leverage do not have significant effect. Keywords: OJK (Otoritas Jasa Keuangan), Debt Proportion, DES